High heat - Karre, Andrew (Andrew Wade), 1978- (Travel team., 2012)
Seth Carter is a star pitcher for his travel team, having gotten "Tommy John" surgery on his elbow in order to throw ninety mile-per-hour pitches. One day a pitch got away from him and hit a kid right on the skull. Ever since, no one has trusted Seth to be a good pitcher, but the biggest game of his life is coming up and he is eager to show his skills once again.